Seismic Performance of an Elevated Water Tank by Employing Fluid Viscous Dampers Considering Hydrodynamic Effect - Bhattarai, Shraddha; Suwal, Rajan (Himalayan Journal of Applied Science and Engineering, 2025)
For water supply and storage systems, elevated water tanks are essential infrastructure. They can be the only source of water in times of emergency, so it is imperative that they keep functioning. With a huge mass at the top of slender columns, they act like an inverted pendulum. The design of the elevated water tank is compromised because, in most cases, designers only take consideration of the hydrostatic effect of water, ignoring the hydrodynamic effect. Thus, the hydrodynamic effect of water has been considered in this study. This study examines three different stagings for a rectangular tank with a 4 m water tank height and a 3 m staging height: 6, 9, and 12 for empty and full tank situations. The fluid viscous dampers (FVDs) in the tank are also considered in this study. FVD is a device that absorbs seismic vibrations. They can be utilized for both the retrofit as well as the new design. ETABs 2020 have been used in the analysis to ensure the tank’s seismic performance. The study shows that base shear, modal mass participation, story displacement, inter-story drift, and damping all improved when FVDs were installed.